Beyond the case the logics and practices of comparative ethnography (New York Oxford University Press, 2020)
"The social sciences have seen a substantial increase in comparative and multi-sited ethnographic projects over the last three decades. Yet, at present, researchers seeking to design comparative field projects have few scholarly works detailing how comparison is conducted in divergent ethnographic approaches. In Beyond the Case, Corey M. Abramson and Neil Gong have gathered together several experts in field research to address these issues by showing how practitioners employing contemporary iterations of ethnographic traditions such as phenomenology, grounded theory, positivism, and interpretivism, use comparison in their works. The contributors connect the long history of comparative (and anti-comparative) ethnographic approaches to their contemporary uses. By honing in on how ethnographers render sites, groups, or cases analytically commensurable and comparable, Beyond the Case offers a new lens for examining the assumptions, payoffs, and potential drawbacks of different forms of comparative ethnography." |c --From publisher's description.
Introduction : the promise, pitfalls, and practicalities of comparative ethnography / Corey M. Abramson and Neil Gong -- Section 1. The evolution of classic approaches to comparison -- Foundations of the behavioralist approach to comparative participant observation / Martín Sánchez-Jankowski and Corey M. Abramson -- Conducting comparative participant observation : behavioralist procedures and techniques / Corey M. Abramson and Martín Sánchez-Jankowski -- The thematic lens : a formal and cultural framework for comparative ethnographic analysis / Thomas DeGloma and Max Papadantonakis -- Comparative ethnographic views of social structure : the challenge of linking micro and macro levels of analysis / Aaron V. Cicourel -- Section II. New and existing critical approaches to comparison -- An ethnography of comparative ethnography : pathways to three logics of comparison / Ching Kwan Lee -- Critical realism and contrastive ethnography : the curious case of autism in Somali refugee communities / Claire Laurier Decoteau -- Sequential comparisons and the comparative imagination/ Iddo Tavory and Stefan Timmermans -- Section III. Contextualizing comparison -- Using computational tools to enhance comparative ethnography : lessons from scaling ethnography for biomedicine / Alissa Bernstein and Daniel Dohan -- Elite ethnography : studying up or down in US and French sociology / Lynn S. Chancer -- A dialog with Aaron Cicourel on comparative ethnography / Aaron V. Cicourel and Corey M. Abramson -- Conclusion : a comparative analysis of comparative ethnographies / Neil Gong and Corey M. Abramson.
Includes bibliographical references and index.
Keywords: Ethnology; Anthropology